THE EFFORTS TO OVERCOME STUDENTS' MISCONCEPTIONS ON SCIENCE LEARNING SUB-CONCEPT BIOTECHNOLOGY AT MTSPN 4 MEDAN - S Nasution; J Febrina; W Sitanggang (UNIVERSITAS NEGERI MEDAN, 2021)
The purpose of this study was to determine the efforts to overcome students' misconceptions inlearning science, especially in biotechnology material. The method used in this research isdescriptive method with qualitative and quantitative approaches. The research population wasall students of class IX MTsPN 4 Medan in the academic year 2021/2022, totaling 20 people.Determination of data sources/subjects of this research is based on cluster sampling techniquebecause the number of informants is relatively small and random, less than 30 people. Previousresearch literature is also used as additional material. Data collection techniques using test andinterview techniques. Data collection in this study used a test in the form of multiple choiceaccompanied by CRI (Certainty of Response Index). The data obtained from the results of thestudy were then analyzed using descriptive statistical techniques, to distinguish students whounderstand concepts, misconceptions and do not understand concepts. The results obtained thatthere were misconceptions about science lessons, especially biotechnology material in class IXstudents of MTsPN 4 Medan in the 2021 academic year with a level of 15.46% in the subconceptsofbasicprinciplesofbiotechnology,9.81%inconventionalbiotechnology,17.85%inmodernbiotechnology. , and 18.44% in the sub-material of the application of biotechnology.Based on the results of the study, the causes of student misconceptions can occur because ofthe individual himself, the debriefing that students receive and the handbook. Efforts that canbe made to reduce the occurrence of misconceptions are the provision of material according tothe concept, detailed explanations, and discussions.